ANALISIS BUDAYA ORGANISASI PT. POS INDONESIA DALAM MENGHADAPI DIGITALISASI LAYANAN DI KOTA MEDAN - Hana Alasaria Silitonga; Muhammad Imanuddin Kandias Saraan (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the organizational culture implemented by PT. Pos Indonesia in facing the challenges of service digitalization, particularly at the Main Branch Office (KCU) in Medan City. In the rapidly evolving digital era, public organizations such as PT. Pos Indonesia are required to undergo transformation not only in their service systems but also in their values and work culture. This research employs a descriptive qualitative approach, using in-depth interviews with five informants from diverse backgrounds: the finance and general administration manager, the operational manager, the courier and logistics control manager, the front-office staff, and a member of the public as a service user. The data were analyzed using the seven organizational culture indicators by Stephen P. Robbins, which include innovation and risk-taking, attention to detail, outcome orientation, people orientation, team orientation, aggressiveness, and stability. The findings reveal that PT. Pos Indonesia’s organizational culture remains largely bureaucratic and is not yet fully responsive to digital change due to limitations in human resource capacity and financial constraints. Innovation and risk-taking are still limited, attention to service detail is inconsistent, and outcome orientation is often hindered by rigid work systems. Although efforts to strengthen teamwork and foster human-centric public service are evident, the main challenges lie in technological adaptability and under-optimized human resource roles. Therefore, a reform of the organizational culture is needed—one that is not only flexible and dynamic but also aligned with technological advancements and market demands. This effort can be carried out through capacity building of human resources, streamlining bureaucratic procedures, and strengthening managerial commitment to support innovation. The transformation of organizational culture must become an integral part of the digital adaptation strategy, enabling Pos Indonesia to become more responsive, competitive, and relevant within the modern public service ecosystem.